3D printing applications in bone fabrication: a review - Evi J; Siska Oktaviyani; Mahjur Mahjur; Fitri Afriani (Universitas Sultan Ageng Tirtayasa, 2021)
Bone scaffolding is an alternative solution to bone therapy, which is currently being developed in tissue engineering. This effort aims to produce a bone scaffold with a shape and specification according to bone therapy's needs. 3D printing is a scaffold fabrication method with promising prospects because it can produce scaffolding with physical characteristics as needed, both pore and physical. The method used in this article is a formal review to review various national and international literature using articles from 2000 to 2020 with the keywords